A case of Kallmann syndrome. (28th March 2011) - Arkoncel, Maria Luisa Cecilia R; Arkoncel, Francis Raymond P; Lantion-Ang, Frances Lina
Abstract : Kallmann syndrome (KS), a rare genetic disorder, refers to the association between hypogonadotropic hypogonadism and anosmia or hyposmia due to abnormal migration of olfactory axons and gonadotropin-releasing hormone producing neurons. The authors report a case of a 26-year-old Filipino male who presented with eunuchoid body proportion, absence of facial and axillary hair and sparse pubic hair, micropenis and bilaterally descended prepubertal testes. Associated findings were hyposmia, high pitched voice, absence of puncta and smooth philtrum. Hormonal assay showed hypogonadotropic hypogonadism. He has normal male karyotype. Ultrasonography revealed no renal abnormalities. MRI of the brain showed hypoplastic left olfactory bulb and aplastic right olfactory bulb. These findings are characteristic of KS. Androgen replacement with testosterone was started to induce virilisation. Our patient is now on regular follow-up to monitor response to treatment.